Effect of red and blue lights on the stress response and growth performance of juvenile red tilapia (Oreochromis sp.) - Cheah, Siew Siew (2016)
Colour of light is found to have effect on stress response and growth performance of several species of fish. This study evaluated the effect of visible light with longest wavelength (red) and shortest wavelength (blue) on the stress response and growth performance of juvenile red tilapia throughout 23 days of experiment. Red and blue lights as treatment groups while white light as control group were fixed underneath the tank lid and covered with opaque black colour plastic. Blood was withdrawn from fish chosen randomly (n=45) on day 0, 1, 3, 8, 15, and 23 to evaluate the hematological parameters (RBC count, hemoglobin, PCV, MCV, MCHC, WBC count, thrombocytes and plasma protein) and plasma biochemistry (triglycerides, glucose, total protein, albumin, globulin, and major ions- Na, K, Cl). Body length and weight were also measured on day 0 and day 23 of experiment to evaluate the average length gain, body weight gain, specific growth rate and feed conversion rate. The result showed that there was no significant difference on stress response among the red, blue and white lights. Blue light showed significant length gains (P=0.002) as compared to white light although the other growth parameters (body weight gain, specific growth rate and feed conversion rate) were not significant between treatment groups (red and blue lights) and control group (white light).